Teaching in the community: Changing and implementing a new curriculum - Iwama de Mattos, M. C. [UNESP]; Machado, José Lucio Martins [UNESP]; Ruiz, Tânia [UNESP] (My University, 1998)
The Faculdade de Medicina de Botucatu is changing to, and implementing a new curriculum aimed at integrating teaching and learning in the community. Emphasis is on preparing the community settings for teaching, learning and providing health care. A particular task is staff development with emphasis on problem-based learning (PBL) and training medical and nursing students in the leadership to participate in this process. The new curriculum includes the gradual introduction of clinical practice during First Year, integration of the basic sciences with clinical sciences, through integrated modules studied in small groups, and maintenance of the two year clerkship. The undergraduates are introduced gradually to the community: 8% of the total curriculum during First Year, 10% during Second Year, 10% during Third Year, 20% during Fourth Year, 30% during Fifth and Sixth Years. The basic health units at primary care level, and the regional specialty outpatients and hospitals at the second level, are the main teaching sites. An Education Development Committee was established to discuss the strategies for supporting the changes and to structure the planning for promoting the gradual transformation of staff development. After 18 months of implementation of the curriculum, there followed discussions and monitoring of the objectives of changes in medical education at our school. Successful implementation of the new curriculum would fail, if the objectives were not absorbed by every member of the implementation Committee.
Keywords: brazil; clinical practice; community; curriculum; health care delivery; hospital; leadership; learning; medical education; nursing education; outpatient; personnel management; planning; primary medical care; priority journal; review; teaching